2009
DOI: 10.1055/s-0028-1128150
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and All-cause Mortality: An Updated Meta-analysis with Different Intensity Categories

Abstract: In a meta-analysis we investigated the effect of physical activity with different intensity categories on all-cause mortality. Many studies have reported positive effects of regular physical activity on primary prevention. This recent meta-analysis analyzed all-cause mortality with special reference to intensity categories. A computerized systematic literature search was performed in EMBASE, PUBMED, and MEDLINE data bases (1990-2006) for prospective cohort studies on physical leisure activity. Thirty-eight stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
250
5
26

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 443 publications
(295 citation statements)
references
References 27 publications
14
250
5
26
Order By: Relevance
“…Previous studies have revealed that high aerobic capacity and/or high physical activity levels are strongly associated with long lifespan in humans (Lollgen et al, 2009;. Recently, it was also reported that high intrinsic aerobic capacity is strongly linked to longevity in rodents .…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have revealed that high aerobic capacity and/or high physical activity levels are strongly associated with long lifespan in humans (Lollgen et al, 2009;. Recently, it was also reported that high intrinsic aerobic capacity is strongly linked to longevity in rodents .…”
Section: Introductionmentioning
confidence: 97%
“…While there was a decrease in cancer mortality with higher physical activity levels in men Laukkanen et al, 2011;Orsini et al, 2008), evidence was less clear in women . In contrast, evidence for all-cause and CVD mortality is more consistent (Lollgen et al, 2009;Nocon et al, 2008;Woodcock et al, 2011). A meta-analysis showed a risk reduction of 35% for CVD mortality and of 33% for all-cause mortality in the most active compared to the least active participants (Nocon et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…These studies have shown that regular activity can contribute to the prevention of certain chronic diseases (Warburton et al 2006), the maintenance of mental well-being (Penedo and Dahn 2005), and improvements in survival among people of all ages (Löllgen et al 2009). Current public health policies rate physical activity together with diet as the most critical issues in health promotion, especially in light of the increasing prevalence of obesity and diabetes in many high-income countries.…”
Section: Physical Activitymentioning
confidence: 99%